Balinese ancestral traditions negotiating cultural preservation, commodification, and resilience in Bali’s modern tourism economy - Ida Ayu Ketut Sintia Dewi; Ni Nyoman Supiatni; I Gusti Lanang Suta Artatanaya (Journal of Commerce, Management, and Tourism Studies, 2026)
Balinese tourism depends on ancestral traditions, yet modernization and commercialization increasingly reshape religious, spatial, and artistic practices. This study aims to analyse how Balinese ancestral traditions are preserved, commodified, and creatively adapted within contemporary tourism development, and how these processes affect identity, space, and local wisdom. Using a qualitative approach, it synthesizes empirical legal studies of customary villages, ethnographic and architectural research on traditional houses and homestays, and cultural analyses of myths, dance, and spiritual practices. The analysis compares transformation patterns in architecture and rituals, the management of customary land and village tourism, and strategies of cultural resilience such as Tri Hita Karana–based regulation and adaptive ritual practice. Findings show a paradox: tourism can erode meanings, spiritual depth, and livelihoods, while simultaneously motivating reconstruction, innovation, and strategic filtering of external influences. The conclusion argues that sustainable Balinese tourism requires community-led, regulation-supported models that prioritize living traditions over purely aesthetic cultural display.